FRI0256 ASSESSING THE PREVALENCE AND USE OF VALIDATED SYSTEMIC LUPUS ERYTHEMATOSUS DISEASE ACTIVITY METRICS IN REAL WORLD PRACTICE. (June 2019) - Costenbader, Karen; Hoskin, Ben; Atkinson, Christian; Bell, David; Massey, Olivia; Lofland, Jennifer H.; Berry, Pam; Karyekar, Chetan; Touma, Zahi
Abstract : Background: Disease activity metrics for systemic lupus erythematosus (SLE) are not widely used in real world clinical practice. Objectives: To assess the use and drivers of SLEDAI and BILAG index in real world clinical practice. Methods: A cross-sectional study of rheumatologists in the US and EU5. Data were collected from the Adelphi Real World 2010/2013/2015 Lupus Disease Specific Programmes (DSP). Physicians were asked to complete an attitudinal survey and patient record forms (PRFs) for the next 5 patients consulting with SLE; the same patients were asked to complete patient self-completion (PSC) forms describing how SLE affected them. PRFs collected data pertaining to the patient's diagnosis, disease history, current clinical outcomes, treatment and management history. PSCs focused on similar data collection and included patient reported outcome measures (PROs) to assess the humanistic burden. 2015 DSP data was used to assess the profile of patients with a SLEDAI assessment were compared to those without a SLEDAI assessment, using Fisher's Exact and Mann-Whitney tests. Similar analysis was also conducted for those with/without BILAG index assessments. 2013 & 2010 DSP datasets were merged, and multiple linear regression was used to assess drivers of SLEDAI and BILAG index utility, respectively. Results: Physicians provided 263 surveys, extracted from the 2015 DSP, indicating that 131 were aware of but did not use the BILAG index, and 92 of physicians were aware of but did not use the SLEDAI. Physicians provided 1376 record forms for SLE patients, extracted from the 2015 DSP; 71 (5.2%) had a BILAG index (1305, 94.8% had no BILAG index), and 373 (27.1%) had had a SLEDAI calculated prospectively (1003, 72.8% had No SLEDAI). Patients with SLEDAI had longer disease duration that patients who did not have a SLEDAI (mean: 6.3 vs. 5.2 years, p=0.007), were less likely to have been described as mild at diagnosis (no SLEDAI mild: 18.7%; SLEDAI mild: 11.3%, p=0.0004) and consulted more with health care professionals in the past 12 months (no SLEDAI mean visits: 6.5, SLEDAI mean: 7.7, p<0.001). Patients with a BILAG index had flared more in the last 12 months (no BILAG: 30.6%, BILAG: 45.1%, p=0.0126). Physicians provided data on 220 SLEDAI and 75 BILAG assessments, extracted from the 2010 & 2013 DSPs. Multiple linear regression analyses revealed that flaring in the last 12 months (Coef: 3.27 [0.36 – 6.18], p=0.028), renal symptoms (Coef: 5.67 [1.84-9.51], p=0.004), and muscular symptoms (Coef: 4.58 [1.22-7.94], p=0.008) were all associated with a higher SLEDAI score, with r-squared 0.1948. Multiple linear regression showed that renal symptoms (Coef: 3.87 [1.00 – 6.75], p=0.009) were associated with a higher BILAG score, with r-squared 0.3717. Conclusion: The use of SLEDAI and BILAG index in clinical practice is limited and seemingly reserved for use in more severe patient cohorts; understanding the ongoing impact of this selective use on the treatment and management of SLE would be beneficial. Additionally, understanding the drivers and barriers to the use of disease activity metrics is important to improve the management of SLE in the future. Disclosure of Interests: Karen Costenbader: None declared, Ben Hoskin Employee of: Adelphi, Christian Atkinson Employee of: Adelphi, David Bell Employee of: Adelphi, Olivia Massey Employee of: Adelphi Real World, Jennifer H. Lofland Employee of: Janssen Global Commercial Strategic Organization, Pam Berry Shareholder of: GSK and Janssen Global Services, Chetan Karyekar Shareholder of: J&J, Employee of: Janssen Scientific Affairs, LLC, Abbott, BMS, Novartis, Zahi Touma Grant/research support from: GSK Canada, Consultant for: UBC, Pfizer, Janssen, Inc